AL-TAFSĪR AL-SHAFAHI AL-IFTIRĀḌI WA AL-IṢLĀḤ AL-IJTIMĀ‘I: Dirāsah fi Durūs Gus Bahā’ min Khilāl Tafsīr al-Jalālayn (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
This article discusses the important features of social reform contained in the explanation of Sura Yasin, Chapter 36 of the Qur'an through Tafsir al-Jalālayn, delivered by Baha' al-Din Nur Salim, known as Gus Baha'. It places Gus Baha's interpretation within hypothetical oral interpretation, which Nadia al-Ouznaji calls a type of interpretation that relies on direct discourse between the interpreter and the audience and is based on using the Qur'anic text in a dynamic, realistic way to reform the individual and society. As a qualitative research, it uses recordings of the interpretation of Surat Yasin by Tafsir al-Jalālayn uploaded on the Muhibbin Youtube channel as a primary source. Using a descriptive analytical approach, this research found that Gus Baha's oral interpretation is closely related to social reform because it is in direct contact with the reality of society and generates an impact on people to achieve a reformist goal. Secondly, Gus Baha's explanation of Surah Yus through Tafsir al-Jalālayn contains directives and instructions that call for the reform of individuals and society in various aspects and levels of doctrinal, moral, educational, and social reform. Thus, this research supports Al-Waznaji's argument that oral exegesis is closely related to the task of reforming society.